Muslim consumers’ attitudes toward the advertisement of non-certified coffee shops - Shaizatulaqma Kamalul Ariffin,; Khairul Anuar Mohammad Shah,; Ishak Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2016)
In Malaysia, the Halal logo and certification has a significant religious cue that might peripherally generate a favourable attitude towards advertisement among Muslims. Prior findings have stated that Islamic religious symbol influenced Muslim consumers’ favourable attitude towards the advertising. Advertisements that portray value positions consistent with the intended consumers are likely to be more influential than advertisements that portray inconsistent values. This study intends to examine the relationship of consumers’ attitude functions (utilitarian, value-expressive, ego-defensive, knowledge), attitude towards advertising and purchase intention toward non-certified coffee shops amongst Muslim Postgraduate students in Malaysia. This study applied the Functional Theory of Attitudes to support this framework. Data were collected through self-administered surveys and a total of 242 usable responses were accepted for the purpose of this study. The results of this study show that the value expressive and utilitarian propositions significantly influence consumers’ attitudes toward the advertisement of non-certified coffee shops, whereas attitude towards advertising has a significant impact on purchase intention.